2000
DOI: 10.1097/00003643-200003000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to pulmonary artery catheterization

Abstract: This study compares prospectively the cardiovascular and catecholamine responses to central venous and pulmonary artery catheterization before and after induction of general anaesthesia. Twenty patients for elective coronary artery surgery were randomized into two groups. One group had central venous and pulmonary artery catheterization performed awake using local anaesthesia. The other group had these catheters inserted following induction of general anesthaesia. In all patients heart rate, arterial blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In a study comparing placement of a PAC in a small group of anesthetized versus sedated patients undergoing elective cardiac surgery, O'Connor et al (10) showed no significant differences in hemodynamics and no differences in the stress response to PAC placement between groups. Our study showed that there was no difference in percentage change of MAP during PAC placement between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing placement of a PAC in a small group of anesthetized versus sedated patients undergoing elective cardiac surgery, O'Connor et al (10) showed no significant differences in hemodynamics and no differences in the stress response to PAC placement between groups. Our study showed that there was no difference in percentage change of MAP during PAC placement between groups.…”
Section: Discussionmentioning
confidence: 99%